Unusual metastasis of esophageal cancer - Vidović, Vladimir; Nikolić, Ivan; Vukojević, Jelana; Samardžija, Golub; Kukić, Biljana; Bogdanović, Bogdan; Petrović, Nemanja (Vojnosanitetski pregled, 2014)
Introduction. Carcinoma of the esophagus is in the eighth place by the frequency of malignant diseases and the sixth cause of death from cancer worldwide. It usually metastasizes to regional lymph nodes, liver, lungs, central nervous system, and bones, but metastases can appear to unusual locations such as facial skin and lips. Case report. We presented a 56-year-old man who reported to his physician because of upper lip swelling. A physical checkup of the patients also showed a lesion on the skin of the left temporal region and both lesions were biopsied. Based on the results of histopathological and immunohistochemical analyses of the samples a diagnosis of metastatic adenocarcinoma to the skin was established. Additional diagnostic procedures, including esophagogastroduodenoscopy, detected the infiltration into the distal part of esophagus, which was histopathologically confirmed as adenocarcinoma of esophagus. The results of positron emission tomography/computed tomography (PET/CT) examination showed the invasion of the disease. Because of the disease expansion, a multidisciplinary oncology team suggested chemo- and radiotherapy treatment. The patient has received 4 cycles of platinum-based chemotherapy so far. Conclusion. The physicians should always consider unusual skin lesions as the first sign of cancer spreading.